The role of hospital organizational factors in improving patient-important outcomes of critically ill patients - Mat Nor, Mohd Basri (Malaysian Society of Anaesthesiologists, 2017)
For critically ill patients, a patient-important outcome such as quality of life is more meaningful than just survival. Among important factors that affect outcomes are hospital organization, early recognition of deteriorating patients and avoiding unplanned ICU discharges. The triad of early recognition of deteriorating patients, timeliness of response and activation of clinicians with appropriate clinical competency are the key aspects of Rapid Response System (RRS). RRS has been shown to improve outcomes of critically ill patients in developed countries. To date, there is no formal policy or information on RRS in hospitals across Malaysia. The increased demand for ICU beds is reflected by increased after-hours discharges. Our observational study of ICU admissions over five years has clearly demonstrated an association between after-hours ICU discharge and increased odds of in-hospital mortality. This poses a major concern given that one in every three ICU patients is being discharged after-hours in Malaysia.